Distinct recruitment of human eIF4E isoforms to processing bodies and stress granules - Frydryskova, Klara; Masek, Tomas; Borcin, Katerina; Mrvova, Silvia; Venturi, Veronica; Pospisek, Martin (BMC molecular biology, 2016)
BACKGROUND: Eukaryotic translation initiation factor 4E (eIF4E) plays a pivotal role in the control of cap-dependent translation initiation, modulates the fate of specific mRNAs, occurs in processing bodies (PBs) and is required for formation of stress granules (SGs). In this study, we focused on the subcellular localization of a representative compendium of eIF4E protein isoforms, particularly on the less studied members of the human eIF4E protein family, eIF4E2 and eIF4E3. RESULTS: We showed that unlike eIF4E1, its less studied isoform eIF4E3_A, encoded by human chromosome 3, localized to stress granules but not PBs upon both heat shock and arsenite stress. Furthermore, we found that eIF4E3_A interacts with human translation initiation factors eIF4G1, eIF4G3 and PABP1 in vivo and sediments into the same fractions as canonical eIF4E1 during polysome analysis in sucrose gradients. Contrary to this finding, the truncated human eIF4E3 isoform, eIF4E3_B, showed no localization to SGs and no binding to eIF4G. We also highlighted that eIF4E2 may exhibit distinct functions under different stresses as it readily localizes to P-bodies during arsenite and heat stresses, whereas it is redirected to stress granules only upon heat shock. We extended our study to a number of protein variants, arising from alternative mRNA splicing, of each of the three eIF4E isoforms. Our results surprisingly uncovered differences in the ability of eIF4E1_1 and eIF4E1_3 to form stress granules in response to cellular stresses. CONCLUSION: Our comparison of all three human eIF4E isoforms and their protein variants enriches the intriguing spectrum of roles attributed to the eukaryotic initiation translation factors of the 4E family, which exhibit a distinctive localization within different RNA granules under different stresses. The localization of eIF4E3_A to stress granules, but not to processing bodies, along with its binding to eIF4G and PABP1 suggests a role of human eIF4E3_A in translation initiation rather than its involvement in a translational repression and mRNA decay and turnover. The localization of eIF4E2 to stress granules under heat shock but not arsenite stress indicates its distinct function in cellular response to these stresses and points to the variable protein content of SGs as a consequence of different stress insults.
Keywords: Translation control; Eukaryotic translation initiation factor 4E (eIF4E); Heat-Shock Response; Translation initiation factor; buněčné linie; Poly(A)-Binding Protein I; oxidační stres; HEK293 Cells; PB; poly(A)-vazebný protein I; Eukaryotic Initiation Factor-4E; sekvence aminokyselin; eIF4E2; Oxidative Stress; eIF4E3; lidé; Arsenite; Stress granule; RNA Cap-Binding Proteins; proteiny vázající čepičku mRNA; Heat shock; messenger RNA; Amino Acid Sequence; HEK293 buňky; Cell Line; RNA, Messenger; SG; Cloning, Molecular; Sequence Alignment; reakce na tepelný šok; cytosol; klonování DNA; Cytosol; sekvenční seřazení; eukaryotický iniciační faktor 4E; Processing body (P-body); Humans